The Influence of Reading Activities on Grade VI Elementary School Students’ Reading Skills Regarding Electrical Energy via RADEC Learning - Robby Candra Firmansyah; Wahyu Sopandi; Atep Sujana (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
Reading is one of post activity stage activities in the RADEC model. This study aims to investigate the impact of reading on reading skills. The methodology is descriptive quantitative and makes use survey techniques and learning evaluation tests. Intentionally employed in the sample were 26 students from a Bandung elementary, 12 of whom male and 14 years old. In order to conduct reading activities using Google Forms and assess the practicality of reading, this study's analytical technique comprises figuring out the average value of content comprehension on pre-learning examinations and evaluation tests. The analysis's results show that typical student's pre-learning understanding was demonstrated by their average evaluation test scores, which were 80 and 8 when they read 75% of the material, 76.7 and 67.8 when they read 50% of the material, and 62.5 and 42.5 for those who read 25% of the material. The study's conclusions indicate that the reading activities in the RADEC model have an effect on students' comprehension skills. How thoroughly and effectively you read the content will determine how well you will understand it. The results of this study will be utilized as research material to evaluate how effectively classroom training prepares students for reading-related activities.